Imam Al-Jazuli's dala'il al-khayrat wa shawariq al-anwar : an analitical and comparative study of six manuscripts - Nurul Iman binti Rusli (International Institute of Islamic Thought and Civilization, International Islamic University Malaysia, 2015)
This dissertation is an analytical and comparative study of copies of Dala'il al-Khayrat from the Maghrib and the Mashriq of the Islamic land, with the emphasis on the six out of nineteen copies from the collection of Islamic Arts Museum Malaysia. The Dala'il al-Khayrat is a renowned Salawat, collection of prayers and blessing to the Prophet Muhammad (P.B.U.H.), which was written by the 15th century Moroccan Sufi and scholar, Imam al-Jazuli (d. 1465 AD / 870 AH). Later, copies of this Salawat were produced in different part of Islamic lands, in Turkey, Indian Subcontinent, Central Asia and Southeast Asia. The text is divided into sections for daily recitation. Most manuscript of Dala'il al-Khayrat have either illustrations of the RawÌah and the Minbar or the view of the holy mosques in Mecca and Medina. Most copies of this manuscript are also illuminated, served to mark the beginning or the end of the sections of prayer. In this dissertation, the focus will be on the illustrations. This is coupled with an examination on the areas of illumination found within the manuscripts, besides the division of the text. Adopting the historical and descriptive research method, the six copies of Dala'il al-Khayrat — three of these copies were produced in Morocco and the remaining is from the Malay world — were analysed and comparisons between copies produced in this two regions were made. Further attention were given to the two out of six Maghrib and Mashriq copies of Dala'il al-Khayrat, with the reference number IAMM 2012.11.16 and IAMM 1998.1.790. The findings of this dissertation had answered all the research questions. Copies of the Dala'il al-Khayrat manuscript were not isolated from the tradition of manuscript production in a specific region of the Islamic land. Distinctive patterns of illustrations and style of illumination received the influences from the bookmaking ateliers at their respective provenances. Aesthetically, it received a similar treatment as its Qur'anic manuscript counterparts.